Arah Pembangunan Hukum Keluarga Islam Indonesia: Pendekatan Integratif dan Interkonektif dalam Membangun Keluarga Sakinah - Khoiruddin Nasution (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
So far the subjects discussed in Islamic Marriage/Family Law (Munakahat) limited marriage matter only and using the normative approach (halal and haram). In fact the successness of family is not enough by merely understanding marriage matter and the normative approach. To build a happy family as the goal of marriage in Islam is required other knowledges and approaches outside the normative approach. Even with other subjects and using multi approach, it is possible to uncover the secret behind the Quranic texts discuss marriage. This paper attempts to illustrate how science Ethnology, as illustrated Hazairin, can reveal the secret behind the Quranic verse discuss mahram (women are forbidden to marry) as it is described in al-Nisa? (4): 22, 23, and 24. Likewise, this paper tries to offer a number of subjects that should be included in the subject of Islamic marriage in order to be able to achieve the goal of marriage and family breakdown can be avoided. To mention some of which are: (1) the science about sexuality and sciences related thereto, (2) the science of reproduction and reproductive health, (3) knowledge of health and family nutrition, and (4) knowledge about building communication between family members.